A Conceptual Framework on the Determinants of Poverty and Its Impact on Households in Pakistan - Tasleem , Zerish; Ayaz Muhammad, Sohail; Saif, Aiza (Sociological Research And Innovation, 2025)
This paper discusses the multifaceted impact of socioeconomic problems, including low incomes, poor education, joblessness, and widespread poverty, on the effectiveness of the government in fulfilling its role as a governing and regulating agency. More than half of the population in urban and rural Pakistan subsists in poverty, which remains a grave challenge to the stability and advancement of the nation. Not only do these socioeconomic constraints compromise the health of individuals and communities, but also increase the challenges for the government to implement development programs, enforce laws, and maintain social order. Based on data collected from a cross-sectional survey administered to a statistically selected sample of 384 households, the study takes a quantitative approach. The Statistical Package for the Social Sciences (SPSS) was applied to analyze the data in order to identify trends and relationships between factors related to poverty and the effectiveness of the government. Findings reveal that the combination of low income, high unemployment, and poor education significantly incapacitates public compliance and institutional authority. By offering empirical evidence highlighting the compelling interrelationship between socioeconomic adversity and government functionality, this study contributes to the greater poverty discourse. Further, the research fills a huge gap in the knowledge base regarding the structural impacts of poverty in Pakistan and provides valuable data to social welfare organizations, development planners, and policymakers. The results emphasize the urgent necessity for comprehensive, multi-sectoral strategies to alleviate poverty as well as enhance governance